2019
DOI: 10.1039/c9sm01250h
|View full text |Cite
|
Sign up to set email alerts
|

Microphase separation in oriented polymeric chains at the surface of nanomaterials during nanofiber formation

Abstract: The significance of the configuration of a nanoscale functional surface on the texture of polymeric chain assemblies during electrospinning for controlled flexible scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…It has been established that the phase segregation in TPU can be influenced by the introduction of functional nanofillers and their geometries during nano- and microscale phase separations. , We found here the site-specific hard phase formation in nanometer dimensions due to preferential relocation on functional nanofillers, which is supported by the enhanced scattering intensity around q = 0.8 nm –1 (Figure ). Moreover, it can be clearly seen that with the addition of 1D nanofillers, the hump broadens further, while on adding 2D-functionalized graphene, the hump becomes almost flat.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…It has been established that the phase segregation in TPU can be influenced by the introduction of functional nanofillers and their geometries during nano- and microscale phase separations. , We found here the site-specific hard phase formation in nanometer dimensions due to preferential relocation on functional nanofillers, which is supported by the enhanced scattering intensity around q = 0.8 nm –1 (Figure ). Moreover, it can be clearly seen that with the addition of 1D nanofillers, the hump broadens further, while on adding 2D-functionalized graphene, the hump becomes almost flat.…”
Section: Resultssupporting
confidence: 72%
“…The scale of reinforcement is particularly important for the enhancement of synergistic properties much beyond their intrinsic values. The carbon-based fillers have the unique advantages of low density, availability with a range of shapes and sizes, ease of derivatization, and recyclability. The internal topography of the supramolecular microdomains of TPU is found to be significantly affected by different geometries of low-dimensional carbonaceous nanofillers on various functional surfaces. Interfacial crystallization in the presence of different geometries of fillers has attracted huge interest in the past, and several hybrid morphologies have been produced and their structure–property studies have been carried out. , It has been found that fillers are mainly localized in the amorphous phase in semicrystalline polymers, as the high degree of crystallinity of polymeric chains resists the fillers to go inside the crystalline region .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Carbon nanoparticles were synthesized from graphene oxide by concentrated nitric acid treatment. 23 To check the degree of immobilization of nanomaterials into the polymer matrix, the 1D and 2D nanomaterials were combined together to prepare 3D hierarchical structures of MWCNTs immobilized into few layer graphene flakes. 24 The different geometries of nanofillers and their analysis are described in the ESI† (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Hierarchical nanostructured materials are composites comprised with various functional phases and interfaces [6,7,8,9]. In the resultant hierarchical nanomaterials, combination of different phases with electrical/magnetic/mechanical/optical functions leads to new properties that cannot be found in conventional materials [10,11,12,13]. However, the fabrication of composite structure through the combination of functionalized phases or confined different nanomaterials in space of few nanometers is still very challenging [14].…”
Section: Introductionmentioning
confidence: 99%